PERANCANGAN DAN IMPLEMENTASI ALAT PENGECEKAN KABEL NURSECALL BERBIAYA RENDAH SEBAGAI ALTERNATIF MULTIMETER - Abdul Latif; Kusnanto Mukti Wibowo; Royan - (Jurnal Ilmiah Poli Rekayasa, 2025)
Cables in nurse call systems generally have considerable length and are distributed across multiple installation points, making them vulnerable to faults such as broken wires, loose connections, or continuity problems. These conditions can disrupt communication between patients and medical staff, potentially reducing the quality of healthcare services. Therefore, checking cable continuity before and after the installation process is a crucial step to ensure that each line is properly connected and that the nurse call system operates optimally and reliably. This study designs and tests a low-cost prototype device for checking the continuity of nurse call cables, consisting of two modules: Device A as a 9-volt power source and Device B as a two-line LED-based indicator. The novelty of this research lies in the use of a simple non-microcontroller circuit with direct visual indicators, specifically designed for on-site nurse call cable inspection as a practical alternative to conventional multimeters. The research method includes circuit design, prototype development, and field testing on cables with various length variations, followed by a functional comparison with conventional testing methods. The test results indicate that the device is capable of reliably detecting cable conditions through LED indicators that turn on or off during each test, with a high level of consistency. In addition, its low production cost and ease of use provide practical contributions for technicians involved in the installation and maintenance of nurse call systems, particularly in field conditions that require fast and efficient inspection.